Exploring the Pharmacists’ Knowledge, Attitude, and Practice During COVID-19: A KAP Model Approach - Abrar Ghaith; Islam Alghreiz; Tayseer Afifi (Advances in Public Health)
Conclusion: This study highlights the significance of educating pharmacists about evidence-based practices to improve their involvement in COVID-19 prevention and control. The importance of disseminating clear information via a variety of communication methods is underscored by the positive association found between knowledge and practice. The study focuses on pharmacists in Kuwait in particular since it acknowledges the need to bolster their optimistic outlooks and aggressive involvement in tackling health issues. In conclusion, these results highlight how important focused interventions and education are to successful pandemic management.